PERAN LINGKUNGAN DALAM KASUS DEMAM BERDARAH DI KOTA PALEMBANG SUMATERA SELATAN - Tri Wurisastuti; Hotnida Sitorus; Surakhmi Oktavia (SPIRAKEL, 2017)
Palembang is a city that has a case of Dengue Hemorrhagic Fever (DHF) highest in the province of South Sumatra in 2014 that 622 cases. transportation Smoothly,cities are highly developed and densely populated settlements that can cause Palembang to become into top ranking in the number of dengue cases over the years. The purpose of this analysis to determine the factors that influence the dengue cases in Palembang South Sumatera Province by using linear regression modeling. The data is used by health profile of Palembang City in 2014. The sample in this analysis are all health centers in the working area of ​​Palembang City Health Department. Response variable is the number of dengue cases in each health center in the region of Palembang City Health Department. Data were analyzed using multiple linear regression analysis. The analysis showed that the factors affecting dengue in the city of Palembang were the number of group counseling activities per month. Increased group counseling activities per month can reduce dengue cases in the city of Palembang every year. Therefore it is considered necessary to increase the number of distillation activities about dengue to the people of Palembang City who live in densely populated areas. In counseling it is also necessary to apply 3M PLUS or implement PSN to the environment that can break the chain of Aedes aegypti mosquitoes and propagation.